2022
DOI: 10.3389/fpls.2022.804145
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Putative Markers of Non-infectious Bud Failure in Almond [Prunus dulcis (Mill.) D.A. Webb] Through Genome Wide DNA Methylation Profiling and Gene Expression Analysis in an Almond × Peach Hybrid Population

Abstract: Almond [Prunus dulcis (Mill.) D.A. Webb] is an economically important nut crop susceptible to the genetic disorder, Non-infectious Bud Failure (NBF). Despite the severity of exhibition in several prominent almond cultivars, no causal mechanism has been identified underlying NBF development. The disorder is hypothesized to be associated with differential DNA methylation patterns based on patterns of inheritance (i.e., via sexual reproduction and clonal propagation) and previous work profiling methylation in aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…However, further work has been done to clarify the link between DNA methylation and the exhibition of NBF in almond. This work includes comparative epigenomics of homozygotic twins with divergent exhibition of NBF (D'Amico‐Willman, Niederhuth, Willman, et al., 2021), whole‐genome DNA methylation and transcriptomic reconfigurations during aging of almond seedlings (D'Amico‐Willman, Niederhuth, Anderson, et al., 2021), and the identification of (epi)genomic signatures associated with NBF exhibition in almond × peach progenies with a 1:1 NBF segregation ratio (D'Amico‐Willman, Sideli, et al., 2022).…”
Section: Epigenetics In Almondmentioning
confidence: 99%
“…However, further work has been done to clarify the link between DNA methylation and the exhibition of NBF in almond. This work includes comparative epigenomics of homozygotic twins with divergent exhibition of NBF (D'Amico‐Willman, Niederhuth, Willman, et al., 2021), whole‐genome DNA methylation and transcriptomic reconfigurations during aging of almond seedlings (D'Amico‐Willman, Niederhuth, Anderson, et al., 2021), and the identification of (epi)genomic signatures associated with NBF exhibition in almond × peach progenies with a 1:1 NBF segregation ratio (D'Amico‐Willman, Sideli, et al., 2022).…”
Section: Epigenetics In Almondmentioning
confidence: 99%
“…There are no major differences in the TE methylation levels but they found some DMRs that overlap with certain families of LTR retrotransposons that are demethylated in the hybrid compared to peach only in the CHG context but without an associated transcriptional reactivation. Using different parents of the same species, D’Amico-Willman et al (2022) [ 129 ] observed that the overall levels of methylation did not differ in the hybrid, although they identified DMRs in each methylation context, some of them associated with TEs. However, these DMRs vary in different individuals of the F1.…”
Section: Changes In the Epigenetic Silencing Of The Tes In Plant Inte...mentioning
confidence: 99%
“…The whole genome sequences of Prunus dulcis cv “Texas” [ 12 ] and Prunus dulcis cv “Lauranne” [ 13 ] were published and are available on the GDR database ( accessed on 1 January 2021), and recently another whole genome cv “Nonpareil” was also published [ 14 ]. In addition to the sequencing of the “Texas” genome, the “almond genome” consortium has resequenced several almond cultivars using paired-end Illumina sequencing, allowing the detection of a high number of SNPs and InDel variants.…”
Section: Introductionmentioning
confidence: 99%